Damage Induced by Recycled Aggregates on the Short-Term Tensile Behaviour of a High-Strength Geotextile. (2016) - Vieira, Castorina Silva; Lopes, Maria de Lurdes
Abstract: This paper presents the mechanical, chemical and environmental degradation induced by recycled Construction and Demolition Wastes (C&DW) on the short-term tensile behaviour of a nonwoven polypropylene (PP) geotextile reinforced with polyester (PET) yarns. In order to study the chemical and environmental degradation a damage trial embankment (2m x 3m in plant) was constructed using recycled C&DW as filling material. The damage caused by the mechanical actions during installation was also simulated by installation damage laboratory tests. Wide width tensile tests were performed on geotextile samples exhumed from the trial embankment after 12 months, on laboratory damaged samples and on intact (as-received) samples. Their short-term tensile behaviour is compared. Scanning electron microscope (SEM) images of intact and exhumed specimens are also presented.